PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN PROSES MENULIS DI SEKOLAH DASAR - Ardila, Rosi; Arief, Darnis; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This class action aims at improving the skill of students in writing narrative texts by using the writing process for the 4 grade students of SDN 08 Air PuraPesisirSelatan.the subjects of the research consisted of twenty two 4 grade student of the school. The research result show that there is some improvement. The score of the teacher’s aspect increased from 75% in cycle I to 91% in cycle II. Meanwhile, the score of the student’s aspect increased from 70% to 88% in cycle II. The student’s skill also improved. First, their score in the pre-writing activity increased from 77.68 in cycle I to 88.63 in cycle II.third, the score increased in the post-writing activity from 74,64 in cycle I to 88.63 in cycle II third, the score increased in the post-writing activity from 74.64 in cycleI to 87.14 in cycle II. Thus, the writing process successfully improved the skill of the students in writing narrative texts.Keywords : Narrative writing Skill, the writing Process